Socioeconomic Services of Khampti Tribe of Arunachal Pradesh Concerning Introduction of Homestead Agroforestry - Hazarika, Prosanta; Kotoky, Malaskiva; Suman, Mayur; Hazarika, Protul (International Journal of Bio-resource and Stress Management, 2023)
A socioeconomic survey was done during (2019–2022) in 15 villages of the Khampti tribe of Namsai, Arunachal Pradesh, India. A questionnaire was prepared and interviewed the households about socioeconomic, life style, livelihood, education, primary livelihood activity, land holdings and land use pattern, energy consumption, livestock profile etc.To compare the profitability of different land uses, the annual profit was calculated. More than 50% of the households were lived in kaccha houses, 32% live in semi pucca houses and 15% had pucca houses. Average annual income of the households was maximum (25%) within the range of ` Rs. 15,000–20,000; 23% incomes more than ` 40,000; while 5.3% within the range of `Rs. 10,000–15,000. About 66.66% households were depended on agriculture for their livelihood. Similarly, 20% households were depended on both agriculture and government job, whereas, 1.77% households were dependent only on government jobs and 0.88% on business. 50% population completed their studies up to class 10; 22% had their secondary education (class 12) and few (4.64%) had done post-graduation. Average 73.87% of the total land was used as agricultural land and 25% as homestead land. Cow was the highest reared livestock than pig, goat and buffalo. Annual energy consumption was recorded for LPG (67.55%), fire wood (17.34%) and kerosene (15.11%). Further, their homesteads do not have agroforestry planning to optimize land use. Therefore, we developed five agroforestry demo plots in Namsai district. In the initial years (2020–2022) of agroforestry could enhanced economic return up to 3 times and also widen the livelihood options.